Gastric cancer: epidemiology, biology, and prevention. Issue 5 (September 2019) - Lyons, Kiara; Le, Linh C.; Pham, Yen T.-H.; Borron, Claire; Park, Jong Y.; Tran, Chi T.D.; Tran, Thuan V.; Tran, Huong T.-T.; Vu, Khanh T.; Do, Cuong D.; Pelucchi, Claudio; La Vecchia, Carlo; et al.
Abstract : Gastric cancer is one of the most common causes of cancer-related mortality worldwide. The objective of this article is to review the epidemiology and biology of gastric cancer risk. This literature review explores the biological, clinical, and environmental factors that influence the rates of this disease and discuss the different intervention methods that may not only increase the awareness of gastric cancer but also increase screening in efforts to reduce the risk of gastric cancer. Helicobacter pylori infection is the primary risk factor for gastric cancer. Additional risk factors include geographical location, age, sex, smoking, socioeconomic status, dietary intake, and genetics. Primary and secondary prevention strategies such as dietary modifications and screenings are important measures for reducing the risk of gastric cancer. Interventions, such as H. pylori eradication through chemoprevention trials, have shown some potential as a preventative strategy. Although knowledge about gastric cancer risk has greatly increased, future research is warranted on the differentiation of gastric cancer epidemiology by subsite and exploring the interactions between H. pylori infection, genetics, and environmental factors. Better understanding of these relationships can help researchers determine the most effective intervention strategies for reducing the risk of this disease.